Pengaruh Green Marketing dan Environmental Awareness terhadap Purchase Decision Produk The Body Shop di Mall Olympic Garden Kota Malang - Azizah Faradila; Achmad Zaini; Ita Rifani Permatasari (SM Institute, 2026)
Environmental problems arising from packaging waste have encouraged cosmetic companies to implement Green Marketing strategies and strengthen consumers’ Environmental Awareness. The Body Shop has introduced recycled packaging, the Bring Back Our Bottles program, and refill stations, although consumers still frequently prioritize product quality in their purchasing considerations. This study examined the effects of Green Marketing and Environmental Awareness on the Purchase Decision of The Body Shop products at Mall Olympic Garden, Malang City. An explanatory quantitative design was applied. The population consisted of 13,200 consumers, and 100 respondents were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression, partial tests, a simultaneous test, and the coefficient of determination using SPSS version 26. Green Marketing had a positive and significant effect on Purchase Decision, with a coefficient of 0.488 and a t-value of 4.218. Environmental Awareness also had a positive and significant effect, with a coefficient of 0.775 and a t-value of 5.539. Together, both variables had a significant effect, as indicated by an F-value of 112.818. The Adjusted R Square value of 0.693 shows that the model explains 69.3% of the variation in Purchase Decision. Environmental Awareness was the more dominant predictor. The findings indicate that environmentally responsible purchasing is strengthened by consistent green marketing, acceptable pricing policies, and environmental education that encourages concrete consumer participation.